Efek Edukasi Peer Group terhadap Kesiapan Anak Sekolah Dasar Menghadapi Menarche - Apriani, Desi; Wisanti, Eka (Journal of Bionursing, 2024)
Background. School-age children are preadolescents where girls reach physical maturity and experience menarche. Children who are not ready to face menarche arise problems, one of which is the rejection of menarche, to overcome this problem one of them is by conducting education with peer group methods that are suitable for school-age children. Objective: The purpose of this scientific paper is to determine the effect of Peer Group on Readiness to Face Menarche in Elementary School Students. Method: This research method is quasi-experimental. Total 34 samples were divided into a half intervention group and control group. Hypothesis was tested with t test analysis. Results: The results of the analysis using the paired t test test for the experimental group, the average pre-test was 10.50 and the post-test was 13.50, and the p value was 0.04 (p <0.05) meaning that there was an effect of education with the peer group method on readiness to face menarche. Meanwhile, in the control group the mean of pre-test and post-test was 8.75 and the p-value was 0.39 (p>0.05. Conclusion: There was no significant difference in the control group. This study suggests to the Simpang Tiga Pekanbaru Health Center so that education with the Peer Group method can be taught to school-age children.